Respuesta :

Part (a)

Answers:  

  • g ' (2) = 32
  • y = 32x-44

-----------------------------------

Work Shown:

Refer to figure 1 in the screenshot attached below.

========================================================

Part (b)

Answers:  

  • h ' (2) = -2
  • y = -2x+9

-----------------------------------

Work Shown:

Refer to figure 2 in the screenshot attached below.

Correction:

The derivative for h should be

[tex]h(x) = f(x)*(x-1)^{-1}\\\\h'(x) = \frac{d}{dx}[f(x)*(x-1)^{-1}]\\\\h'(x) = \frac{d}{dx}[f(x)]*(x-1)^{-1}+f(x)*\frac{d}{dx}[(x-1)^{-1}]\\\\h'(x) = f'(x)*(x-1)^{-1}+f(x)*(-1(x-1)^{-2})\\\\[/tex]

I had a -2 in there instead of -1 as the coefficient.

You should find that h ' (2) = -2

That would then lead to y = -2x+9

The steps shown in figure 2 are effectively the same, just with different numbers of course.

Ver imagen jimthompson5910
Ver imagen jimthompson5910